Letter draft from Max Bredig to Fritz Haber, June 1928 - Bredig, Max Albert (1928)
Max Bredig (1902-1977) drafts a letter to Fritz Haber (1868-1934) regarding potential employment in his laboratory.
Keywords: Bredig, Max Albert, 1902-1977; Haber, Fritz, 1868-1934; Applications for positions